Udział Wojewody Dolnośląskiego w kształtowaniu bezpieczeństwa państwa i porządku publicznego w związku z migracją cudzoziemców - Bruder, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article focuses on the contribution of the Governor of the Lower Silesian Province to national security and public order in connection with migrations of foreigners. It must be noted that the governor, as a representative of the Council of Ministers in the region, is responsible for national security and public order policies, especially with regard to the dynamically evolving social phenomenon of entry into, stay in and departure from the territory of Poland of foreigners as well as citizens of EU member states. Within a short period of time Poland has become a transit or target country for some categories of migrants and nationalities, which is why the governor can effectively shape national security and public order only by cooperating with other public administration bodies. In this respect the governor collaborates with many institutions, most important among them being the Office for Foreigners, Border Guard and other governors. The most crucial element in the process is quick and effective information transfer, which in practice makes it possible to prevent abuses on the part of migrants or abuses in which migrants are the victims.
Keywords: terroryzm; bezpieczeństwo narodowe; migracje; zagrożenia bezpieczeństwa; administracja; samorząd regionalny